Differences of nucleotide and amino acid sequences of nucleoprotein (N) gene between wild-type measles virus and vaccine virus in Indonesia - Made Setiawan; Agus Sjahrurachman; Fera Ibrahim; Agus Suwandono (Indonesian Pediatric Society Publishing House, 2008)
Background Measles virus is a member of genus morbilivirus which belongs to family paramyxovirus with negative, single- strand RNA genome. RNA is packed by nucleocapsid (N) protein. The N protein is very important for RNA replication and translation. Abnormality in N protein will induce abnormality in virus replication. Objective This study aimed to explore the differences of nucleotide sequence of N gene and amino acid sequences of N protein between wild-type measles virus (G2, G3 and D9) and vaccine virus (CAM-70, Schwarz and Edmonston-wt) Methods The exctraction and amplification of the gene were conducted in the laboratory using biomolecular technology. The gene and protein analysis were conducted using the bioinformatic technology. Results The results showed that more differences were found between nucleotide sequences of N gene of wild-type measles virus against CAM-70 vaccine virus (77 - 79 nucleotides) compared against Schwarz and Edmonston-wt vaccine virus (71- 74 nucleotides). Likewise, more differences were also observed between amino acid sequences of N protein of wild-type measles virus against CAM-70 vaccine virus (18-24 residues) compared against Schwarz and Edmonston-wt vaccine virus (17-23 residues).